Analisis Tingkat Kecelakaan Lalu Lintas Pada Ruas Jalan Jenderal Sudirman Desa Aek Batu Kecamatan Torgamba - Pramudya, Ikhsan; Marwan Lubis; Darlina Tanjung (Universitas Nusa Putra, 2025)
A traffic accident event is very diverse both in terms of the process of occurrence and the level of accident. The number of accidents that occurred on the Jendral Sudirman road, Aek Batu Village, Torgamba District, resulted in many losses. On this basis, it is necessary to analyze the accident rate against the high number of accidents so that the accident rate can be known. The research method used in this research is a combined method which uses primary data and secondary data. Data from the Torgamba District Police, from 2019 to 2023, there were 378 traffic accident victims. Results of the percentage analysis of accident rates in the last 5 years, Light Injury (LR) victims were the highest in the accident rate with a percentage value of 62.17% with a total of 235 accident victims, then the number of Serious Injury (LB) victims was 25.93% with the number of victims was 98 accident victims, and the death toll (MD) was 11.9% with the number of victims being 45 accident victims. The results of the correlation coefficient analysis using SPSS to determine the correlation coefficient value for the accident level, it was obtained that the highest Pearson correlation value was found in victims of minor injuries. (LR) is (r) 0.920, which means it is perfectly correlated, with a significance value of 0.027, which means it has a significant relationship with the number of accident victims. Efforts that can be made to reduce the number of accidents are: providing education about traffic and strict sanctions to road users who violate traffic regulations and the installation of traffic signs must be in accordance with Decree of the Minister of Transportation Number 61 1993 concerning Traffic Signs